Automated Control System for Benzine Hydrotreating Block - Melikov, E.A.; Maharramova, T.M. (Herald of Azerbaijan Engineering Academy, 2025)
In the article, minimizing energy losses is identified as a primary challenge for enhancing the productivity of the straight-run benzine hydrotreating process and improving the quality of the resulting target product. The ultimate goal, based on the comprehensive studies carried out, is to obtain high-quality hydrotreated benzine. The physical justification for the studied technological process and the development of a modern automated control system is presented. The development of such an effective automated control system is an actual and important task in the modern oil refining, petrochemical, and chemical industries. The main technological apparatus analyzed in the gasoline hydrotreating unit is the stabilization column. In this case, the minimum and maximum limits of the operating parameters have been established, as it is one of the key devices in the benzine hydrotreating system. After clarified the technological operating modes of the main apparatuses, important regulated and controlled parameters were determined. That is, the main goal of the conducted research is the correct choice for technological parameters of the studied process, their optimal regulation, monitoring, control and, ultimately, obtaining high-quality hydrotreated benzine. Technological and automated schemes for the studied system were developed using the modern graphic platform “Draw.io”.